Tracing The Footprints of Islamic Values Education: Bibliometric Expedition for Future Pathways - Luthfi Syifa' Fauziyah; Nurul Latifatul Inayati; Muhamad Subhi Apriantoro; Afief El Ashfahany; Rozi Irfan Rosyadhi (State Islamic Institute of Madura, 2023)
The purpose of this study is to outline the trajectory and future directions of Islamic values education research as it appears in articles that the Scopus database has indexed. This study used bibliometric analysis techniques to identify all publications registered in the Scopus database on Islamic values ​​education from 1980 to 2023. The data obtained were then analyzed using Excel and either R or R-Studio. Meanwhile, to perform visual analysis related to keywords and citations simultaneously, researchers used VOSviewer. This research shows that the function, subject, and specified criteria were met by 257 papers that the author located on Scopus. In this research, the related topic has an annual growth rate of 3.56%, with the majority of articles coming out in 2020. The nation that has generated the greatest publications on the subject of teaching Islamic values is Indonesia, with Malaysia coming in second. Universiti Kebangsaan Malaysia and Universiti Malaya Malaysia are the Malaysian universities with the two highest connections, respectively. Meanwhile, the writer who is most active in researching the field of Islamic values ​​education is Nuryana, Z. The bibliometric analysis in this study was specifically taken from Scopus. This research provides a brief description of the literature that can be accessed by researchers in the field of Islamic values ​​education and can be used as a reference for relevant research in the future.